A review of the genus Tolpia Walker, 1863 in East Asia with descriptions of five new species (Lepidoptera, Erebidae, Hypenodinae, Micronoctuini). Taxonomic study of Micronoctuini. Contribution VII - Han, Hui Lin; Kononenko, Vladimir S. (Zootaxa, 2023)
The genus Tolpia Walker 1863 is reviewed. Five new species: Tolpia ysbaei sp. n., T. qiongensis sp. n., T. subhainanensis sp. n., T. kohkonga sp. n. and T. michaeli sp. n. are described from South China, Cambodia and Malaysia. New collecting data for other species treated in the article are presented. Among them three species, Tolpia bhutani Fibiger, 2007, T. unguis Fibiger, 2007 and T. sikkimi Fibiger, 2007, are reported from China for the first time and T. multiprocessa Fibiger, 2008 is first reported from Cambodia. Keys for identifying species in the odor, unguis, peniculus, conscitulana and crispus species-groups are presented. The checklist of the genus Tolpia comprises 35 species including newly described species and four incertae sedis.